The level of knowledge of private medical practitioners regarding tuberculosis diagnosis and management in Tshwane, Gauteng - Seaketso, Goitsemodimo Winfred (University of Limpopo ( Medunsa Campus ), 2010)
The management of tuberculosis has undergone a lot of changes from fixed dose tuberculosis regimen, directly observed therapy short-course strategy (DOTS) to the introduction of international standards to tuberculosis care (ISTC) in order to reduce the burden of tuberculosis. The study investigated and described the experiences of private general practitioners regarding the knowledge of diagnosis and management of tuberculosis in Tshwane, Gauteng Province. The purpose of the research was addressed within a quantitative approach applying descriptive designs. A self-administered questionnaire was used to collect the data that fit the objectives of the research. In this study, the population applied to ninety-nine doctors of the Private General (Medical) Practitioners’ profession in a specific urban area, namely the municipal area Tshwane, Gauteng Province, with the following inclusive criteria as study units: practicing as a General Practitioner in Tshwane, which includes the city centre (Pretoria Central), Atteridgeville, Pretoria suburbs, Atteridgeville, Mamelodi, Eersterus, Garankuwa, Mabopane, Odi and Soshanguve and sessions appointment at public hospitals. The researcher drew a representative sample of the private medical practitioners with a random selection process whereby the first general practice in each area was selected randomly, and from there onwards the first three practice rooms, skipping the fourth practice room throughout the Guateng area where 90 private medical practitioners was reached. A total of 90 questionnaires were distributed to General Practitioners in the identified areas of Tshwane, Gauteng Province. A response of 59/90 (66%) was obtained, which compares favourably with the experience of other researchers. The study reveals that national TB guidelines are not properly followed by the respondents and that there is a need for public-private partnership in order to improve and enhance the diagnosis and management of tuberculosis in Tshwane, Gauteng Province.
Thesis (MPH)--University of Limpopo, 2010.
Keywords: Tuberculosis; Medical practitioners; Knowledge; Diagnosis